2015
DOI: 10.1523/jneurosci.0903-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Subanesthetic Doses of Ketamine Cause Sustained Disruptions of NMDA and AMPA-Mediated Frontoparietal Connectivity in Humans

Abstract: Following the discovery of the antidepressant properties of ketamine, there has been a recent resurgence in the interest in this NMDA receptor antagonist. Although detailed animal models of the molecular mechanisms underlying ketamine's effects have emerged, there are few MEG/EEG studies examining the acute subanesthetic effects of ketamine infusion in man. We recorded 275 channel MEG in two experiments (n ϭ 25 human males) examining the effects of subanesthetic ketamine infusion. MEG power spectra revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
183
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(222 citation statements)
references
References 69 publications
34
183
3
2
Order By: Relevance
“…The finding of elevated TC-interactions at beta/gamma-band frequencies is consistent with preclinical data (Dawson et al, 2013), highlighting that acute Ketamine administration affects prominently thalamo-cortical interactions (but see (Muthukumaraswamy et al, 2015) for a recent MEG-study reporting a different finding on connectivity patterns). Moreover, several resting-state fMRI studies reported increased functional connectivity between thalamus and cortical regions (Anticevic et al, 2013a;Hoflich et al, 2015;Klingner et al, 2014;Woodward et al, 2012), albeit some report mixed findings (Woodward et al, 2012).…”
Section: Enter Figures 6 About Heresupporting
confidence: 79%
See 2 more Smart Citations
“…The finding of elevated TC-interactions at beta/gamma-band frequencies is consistent with preclinical data (Dawson et al, 2013), highlighting that acute Ketamine administration affects prominently thalamo-cortical interactions (but see (Muthukumaraswamy et al, 2015) for a recent MEG-study reporting a different finding on connectivity patterns). Moreover, several resting-state fMRI studies reported increased functional connectivity between thalamus and cortical regions (Anticevic et al, 2013a;Hoflich et al, 2015;Klingner et al, 2014;Woodward et al, 2012), albeit some report mixed findings (Woodward et al, 2012).…”
Section: Enter Figures 6 About Heresupporting
confidence: 79%
“…In-vivo and in-vitro electrophysiological studies using NMDA-R antagonists have revealed an increase of spontaneous power at both low (30-60 Hz) and high (60-130 Hz) gamma-band ranges as well as at ripple frequencies (130-200 Hz) (Hunt and Kasicki, 2013)(see also (Hong et al, 2010;Muthukumaraswamy et al, 2015) for similar findings in EEG/MEG-data). Specifically, our findings of enhanced gamma-band activity in the hippocampus and thalamus is consistent with data by Zhang et al (2012) who reported gamma-activity increase after ketamine injection by 308% in the hippocampus and 258% in the thalamus.…”
Section: Enter Figures 4/5 About Herementioning
confidence: 70%
See 1 more Smart Citation
“…A non-invasive method used to assess ketamine-activated circuitry in both humans and rodents is the quantitative electroencephalography (qEEG) measurement of gamma-band power, which is dependent upon activation of fast ionotropic excitatory receptors, including AMPA receptors [28][29][30] . We show that, similar to ketamine, (2R,6R)-HNK administration acutely increases gamma power measured via surface electrodes in vivo (Fig.…”
Section: (2r6r)-hnk Effects On Glutamate Receptorsmentioning
confidence: 99%
“…Wong et al (2016) found that subanesthetic ketamine administration disrupted functional connectivity between the subgenual anterior cingulate cortex, which is involved with the modulation of mood (Davey et al, 2012), and a network cluster involving the thalamus, hippocampus and the retrosplenial cortex. Using a ketamine infusion dose often used for the treatment of depression, Muthukumaraswamy et al (2015) demonstrated reduced functional connectivity in frontoparietal networks concomitant with an increase in blissful feelings. Thus, modulation of brain connectivity patterns might also provide a network-level mechanism for ketamine’s effects on depression.…”
Section: Proposed Mechanisms Of Actionsmentioning
confidence: 99%